ORBIT DIGITAL DALAM MEMBANGUN KOMUNIKASI PUBLIK DI KOTA MEDAN PADA MASA PANDEMI COVID-19 - Antonius Samosir; Besti Rohana; Elok Perwirawati (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2021)
This study is entitled "Digital Orbit in Building Public Communication in Medan City During the Covid-19 Pandemic" This research is to find out and analyze: Digital Orbit in building public communication in Medan City During the Covid-19 Pandemic Period. The research method used is qualitative with a descriptive approach. In this method the researcher described how the situation in the field where the research is carried out. The research was done by using field studies with the process of collecting data through observation, and also interviews with 6 respondents. From the results of the research conducted, it is proven that what is taken is public communication theory, digital media theory, new media theory. This theory relates to the implementation and implications of what has been done by Orbit Digital in building Public Communications in the city of Medan during the Covid-19 pandemic. The research was conducted at the Bumi Jurnalis Orbit Building, Jl. Bumi Asri Complex Dormitory Medan. Informants interviewed were from academics, Orbit Digital journalists, company leaders, editor-in-chief and residents of the city of Medan. From the results of the research conducted, there were 5 main points that became the results of the research, namely strategies, forms, methods, challenges and obstacles as well as the success of Digital Orbit in building Public Communication in the city of Medan during the Covid-19 Pandemic. And how is Orbit Digital in building public communication in the city of Medan. The conclusion is Digital Orbit has developed public communication in the city of Medan during the Covid-19 period. This was stated by the opinion of the informants who considered that Orbit Digital had provided correct and educational news.